2019
DOI: 10.1016/j.jretai.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Let Me Imagine That for You: Transforming the Retail Frontline Through Augmenting Customer Mental Imagery Ability

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
242
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 189 publications
(247 citation statements)
references
References 74 publications
2
242
0
3
Order By: Relevance
“…Mende and Noble (2019) speak about a possible future where consumers crave human-to-human contact because technology becomes so efficient and effective at replacing frontline employees. In addition to Mende and Noble (2019) several recent articles speak to the evolving nature of the retail frontline (Arnold et al 2019;Heller et al 2019;Holmqvist et al 2019;Hughes et al 2019;Singh, Arnold, Brady and Brown 2019); the technologies noted in our typology are further evidence of this evolving retail landscape. Strategic introductions of technologies in our 2 × 2 typology offer ways for retailers and service providers to enhance the customer experience, and be competitive, in this rapidly changing environment.…”
Section: P6mentioning
confidence: 54%
See 1 more Smart Citation
“…Mende and Noble (2019) speak about a possible future where consumers crave human-to-human contact because technology becomes so efficient and effective at replacing frontline employees. In addition to Mende and Noble (2019) several recent articles speak to the evolving nature of the retail frontline (Arnold et al 2019;Heller et al 2019;Holmqvist et al 2019;Hughes et al 2019;Singh, Arnold, Brady and Brown 2019); the technologies noted in our typology are further evidence of this evolving retail landscape. Strategic introductions of technologies in our 2 × 2 typology offer ways for retailers and service providers to enhance the customer experience, and be competitive, in this rapidly changing environment.…”
Section: P6mentioning
confidence: 54%
“…Technology now enables consumers to explore, shop, and evaluate their experiences in ways that did not exist previously (in-store or in an online environment). For example, augmented and virtual reality allow customers to further explore the product and experience it in different settings, thus, enhancing decision convenience (Heller et al 2019). 3-D printers can produce customized products providing greater access convenience.…”
Section: Conveniencementioning
confidence: 99%
“…When consumers perceive product representations as tangible, they feel more at ease, or more comfortable, when deciding on whether to purchase the product. The consumer's affective sense of feeling at ease when making a choice, termed decision comfort, has been highlighted as an important aspect of retailing experiences in general (Parker, Lehmann, and Xie 2016) and in AR experiences in particular (Heller et al 2019;Hilken et al 2017). In our context, decision comfort is a necessary part of the affective behaviour control process that translates mental representations to behaviour intentions.…”
Section: Augmenting Control and Feedback Loops In Active Inferencementioning
confidence: 99%
“…For the studies, participants had augmented sensory control (touch vs. voice) over a wooden chair (Study 1 & 2) and a desk lamp (Study 3 & 4). The choice of the stimulus material was in line with (Heller et al 2019) who identified the chosen stimulus as products that required context to be evaluated. Participants wearing the HoloLens could resize the AR holograms, use full 360-• spherical rotation, adjust the product's position or move it anywhere in the room.…”
Section: Equipmentmentioning
confidence: 99%
“…Many firms, including Amazon, IKEA, and L'Oreal, already rely on augmented reality (AR) to enhance the online experience of their customers (Porter and Heppelmann 2017). By projecting virtual content (e.g., 3D furniture items from an online shop) into the physical environment (e.g., a customer's living space), 1 AR lets customers get a better feel for products, and this makes them feel more comfortable with purchase decisions (Heller et al 2019;Hilken et al 2017). Yet, aside from ratings and reviews, when shopping online customers commonly rely on the advice of friends and family (Zhu et al 2010), which they expect to be able to obtain without having to switch between channels or apps (Brynjolfsson et al 2013).…”
Section: Introductionmentioning
confidence: 99%